Dam-associated multiple-stressor impacts on fungal biomass and richness reveal the initial signs of ecosystem functioning impairment. (January 2016) - Colas, Fanny; Baudoin, Jean-Marc; Chauvet, Eric; Clivot, Hugues; Danger, Michael; Guérold, François; Devin, Simon
Highlights: We examine fungal responses to multiple stressors associated with dams. Experiments have been conducted to identify consequences on higher trophic levels. Fungal-based indicators respond differently to physical and chemical stressors. Fungal responses induce cascading effects on ecosystem functioning. Fungi are proposed as early warning indicators of the ecosystems impairment. Abstract: Global biodiversity is decreasing as a consequence of environmental changes and freshwater ecosystems are among the most threatened. There is an urgent need to identify indicators that are both sensitive to anthropogenic disturbances and predictive of the consequences of biodiversity changes on ecosystem functioning. The fungal compartment associated with decaying leaves is an excellent candidate for this purpose, given its key role in leaf litter breakdown, a major ecosystem process. In this study, we determined the extent to which microbial richness and biomass associated with leaf-decaying leaves could be used to predict impacts of multiple disturbances on ecosystem functioning using dams as models of multi-stressed (i.e. physically and chemically) ecosystems. We conducted in situ and laboratory experiments to assess the response of the microbial compartment associated with decaying leaf litter to multiple stressors associated with dams and consequences on higher trophic levels. First, fungal biomass and taxa richness of communities associated with decaying alder leaf litter were determined at nine field sites. Second, two experiments under laboratory conditions were conducted with conditioned leaves from the field experiment to assess consequences of fungal changes on (1) their direct contribution to leaf litter breakdown by measuring the production of fine particulate organic matter (FPOM), and (2) leaf litter breakdown by two leaf-shredding invertebrates, Gammarus pulex and Allogamus auricollis, by measuring leaf consumption rates and FPOM production. In the absence of contamination, the presence of a dam reduced fungal biomass in reservoirs and downstream reaches. Contaminated sediments significantly affected fungal biomass and taxa richness in reservoirs and appeared to lead to synergistic impacts further downstream. Laboratory experiments evidenced the cascading effects on their contribution to ecosystem functioning (i.e. directly by modifying their performance to breakdown leaf litter and indirectly by modifying shredder performance). This study highlights the sensitivity of fungal-based indicators and their value for aquatic ecosystem bioassessment methodologies, identifying the effects of multiple stressors and reflecting the initial signs of ecosystem functioning impairment. Given the importance of the fate of organic matter stored within reservoirs for ecosystems downstream, the microbial compartment associated with decaying leaves could provide powerful indicators of the integrity of reservoir functioning, with strong potential for use in the risk assessment of multiple stressors associated with dams.